DEA Based Approach To Set Energy Efficiency Target Under PAT Framework: A Case Of Indian Cement Industry - Anoop Singh; Bharat Sharma (The Central European Review of Economics and Management (CEREM), 2018)
Aim: Propose a Data Envelopment Analysis (DEA) based approach to set energy efficiency targets under the Perform, Achieve and Trade (PAT) framework of the Bureau of Energy Efficiency (BEE)~~Design / Research methods: We adopt input-oriented non-controllable DEA model with variable return to scale DEA~Conclusions / findings: Due to the implication of in-house energy conversion, we estimate separate energy efficiency targets based on "purchased energy" as well as "process energy". The later accounts for energy finally used in the production process after in-house energy conversion.~Originality / value of the article: The Bureau of Energy Efficiency (BEE) in India has introduced a market based energy efficiency mechanism under the Perform, Achieve and Trade (PAT) framework. Under this mechanism, energy efficiency certificates can be traded across eight identified sectors thus bringing cost effectiveness to achieve the energy efficiency targets. To implement the scheme, differentiated energy efficiency targets have been set using baseline specific energy consumption. This approach does not account for technical and operational aspects like vintage, scale, output mix and input mix. This study proposes an alternative target setting method based on Data Envelopment Analysis (DEA) which takes into account some of the above mentioned technical and operational differences across the industrial plants. A comparative assessment highlights the efficacy of DEA methodology in implementation of the PAT scheme. We estimate energy efficiency targets based on "purchased energy" as well as "process energy", i.e. that used finally in the production process.~Implications of the research: BEE may adopt the suggested approach to set energy efficiency targets for subsequent cycles under the Perform, Achieve and Trade (PAT) framework.
Keywords: Q48; Q49; 330; energy efficiency target; PAT framework; Data Envelopment Analysis; Indian cement industry